Estimating a size‐specific dose for helical head CT examinations using Monte Carlo simulation methods. Issue 2 (21st December 2018) - Hardy, Anthony J.; Bostani, Maryam; Hernandez, Andrew M.; Zankl, Maria; McCollough, Cynthia; Cagnon, Chris; Boone, John M.; McNitt‐Gray, Michael
Abstract : Purpose: Size‐specific dose estimates (SSDE) conversion factors have been determined by AAPM Report 204 to adjust CTDIvol to account for patient size but were limited to body CT examinations. The purpose of this work was to determine conversion factors that could be used for an SSDE for helical, head CT examinations for patients of different sizes. Methods: Validated Monte Carlo (MC) simulation methods were used to estimate dose to the center of the scan volume from a routine, helical head examination for a group of patient models representing a range of ages and sizes. Ten GSF/ICRP voxelized phantom models and five pediatric voxelized patient models created from CT image data were used in this study. CT scans were simulated using a Siemens multidetector row CT equivalent source model. Scan parameters were taken from the AAPM Routine Head protocols for a fixed tube current (FTC), helical protocol, and scan lengths were adapted to the anatomy of each patient model. MC simulations were performed using mesh tallies to produce voxelized dose distributions for the entire scan volume of each model. Three tally regions were investigated: (1) a small 0.6 cc volume at the center of the scan volume, (2) 0.8–1.0 cm axial slab at the center of the scan volume, and (3) the entire scan volume. Mean dose to brain parenchyma for all three regions was calculated. Mean bone dose and a mass‐weighted average dose, consisting of brain parenchyma and bone, were also calculated for the slab in the central plane and the entire scan volume. All dose measures were then normalized by CTDIvol for the 16 cm phantom (CTDIvol, 16 ). Conversion factors were determined by calculating the relationship between normalized doses and water equivalent diameter ( D w ). Results: CTDIvol, 16 ‐normalized mean brain parenchyma dose values within the 0.6 cc volume, 0.8–1.0 cm central axial slab, and the entire scan volume, when parameterized by D w, had an exponential relationship with a coefficient of determination ( R 2 ) of 0.86, 0.84, and 0.88, respectively. There was no statistically significant difference between the conversion factors resulting from these three different tally regions. Exponential relationships between CTDIvol, 16 ‐normalized mean bone doses had R 2 values of 0.83 and 0.87 for the central slab and for the entire scan volume, respectively. CTDIvol, 16 ‐normalized mass‐weighted average doses had R 2 values of 0.39 and 0.51 for the central slab and for the entire scan volume, respectively. Conclusions: Conversion factors that describe the exponential relationship between CTDIvol, 16 ‐normalized mean brain dose and a size metric ( D w ) for helical head CT examinations have been reported for two different interpretations of the center of the scan volume. These dose descriptors have been extended to describe the dose to bone in the center of the scan volume as well as a mass‐weighted average dose to brain and bone. These may be used, when combined with other efforts, to develop an SSDE dose coefficients for routine, helical head CT examinations.